Cross-network access control mechanism for complex network environment - Fenghua LI; Tianzhu CHEN; Zhen WANG; Linjie ZHANG; Guozhen SHI; Yunchuan GUO (Tongxin xuebao)
Complex network environments,such as space-ground integrated networks,internet of things and complex private networks,have some typical characteristics,e.g.,integration of multi-network and information flow in cross-network.These characteristics bring access control for complex network environment the new requirement of coarse-grained control,sticky policies and inconsistent operation semantics.To satisfy these requirements,cross-network access control mechanism in complex network environments (CACCN) was designed by mapping the cyberspace-oriented access control.First of all,the process of mapping was illustrated using the example of space-ground integrated networks.Next,a management model was proposed to manage the control elements in CACCN and a series of management functions were designed by using Z-notation.The analysis on practical example demonstrates that the mechanism can satisfy a series of access control requirements.